Genetic Evaluation of Patients with Clinically Suspected Hereditary Spastic Paraplegia with Seven Novel Variants - Taha Reşid Özdemir; Pınar Gençpınar; Roza Sarıteke; Safa M Dagdas; Senay Haspolat; Bedile I Tiftikcioglu; Nihal Olgaç Dündar; Berk Özyılmaz (Annals of Indian Academy of Neurology, 2025)
Background and Objectives: Hereditary spastic paraplegia (HSP) is a group of neurodegenerative disorders characterized by genetic and clinical diversity. It often overlaps with other neurological conditions, such as cerebellar ataxia, which complicates diagnosis and highlights the importance of molecular genetic testing. This study aimed to investigate the molecular genetic basis of HSP in patients with clinical suspicion by identifying germline mutations in HSP-related genes and expanding the genetic spectrum of the disease through the discovery of novel variants. Methods: Between 2019 and 2024, 74 patients from 71 families underwent genetic evaluation for germline mutations in 41 HSP-associated genes using a targeted next-generation sequencing panel, with Sanger sequencing performed on family members of patients with identified pathogenic variants to confirm segregation. Results: We identified 23 variants, including six novel likely pathogenic (LP) variants, one novel variant classified as variant of uncertain significance (VUS)-LP, seven known pathogenic variants, and nine VUS. Conclusions: Overlapping clinical symptoms and laboratory findings between HSP and other neurological disorders frequently delay diagnosis, emphasizing the necessity of evaluating germline mutations in HSP genes for patients with suspected HSP to achieve a precise diagnosis. This study also contributes to the literature by reporting seven novel variants, enhancing the genetic understanding of HSP.